Double Diabetes: A Growing Problem Requiring Solutions - Popovic, Djordje S.; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2021)
The growing proportion of type 1 diabetes mellitus (T1DM) patients with clinical features of insulin resistance (IR) has led to the description of a distinctive T1DM subgroup, still unrecognised by current guidelines, called double diabetes, assumingly associated with poorer metabolic phenotype and increased risk of micro- and macrovascular complications. The main goal of identifying double diabetes, estimated to be present in up to half of T1DM patients, is timely implementation of appropriate therapeutic interventions to reduce the increased risk of chronic complications and other adverse metabolic traits associated with this condition. Proposed diagnostic criteria are largely divided into three different groups: family history of type 2 diabetes mellitus (T2DM), obesity/metabolic syndrome, and IR. Estimated glucose disposal rate may prove the most reliable marker of double diabetes. In addition to general measures (diet, physical activity, antihypertensive, and lipid-lowering medications, etc.) and development of new insulin preparations with more hepatic action, double diabetes patients may derive more benefit from agents developed for T2DM. Indeed, such potentially promising agents include glucagon-like peptide-1 receptor agonists, sodium-glucose contrasporter-2 inhibitors, and their combination. We are now awaiting long-term trials assessing metabolic and vascular benefits of these medications in double diabetes.
Keywords: adjunctive therapy; cardiovascular risk; double diabetes; insulin resistance; metabolic syndrome; type 1 diabetes mellitus.